Ophthalmic In Situ Gels with Balsam Poplar Buds Extract: Formulation, Rheological Characterization, and Quality Evaluation - Monika Stanciauskaite; Mindaugas Marksa; Liudas Ivanauskas; Kristina Perminaite; Kristina Ramanauskiene (MDPI AG, 2021)
Balsam poplar buds are a raw material with a high content of polyphenols. Various polyphenols are known for their anti-inflammatory and antioxidant properties. In this study, an aqueous extract of balsam poplar buds was prepared in order to use environmentally friendly and non-aggressive solvents. The aqueous extract was lyophilized, and a 1% aqueous solution of lyophilized balsam poplar buds extract (L1) was prepared. L1 solution was used as a source of polyphenols for the production of ophthalmic in situ gels, so as to develop a product featuring antioxidant properties. Poloxamer 407 (P407) and hydroxypropyl methylcellulose (HPMC) were selected as gelling agents for the in situ gels. In order to select the formulations with the best conditions of use, formulations of different polymer concentrations (P407-10%, 12%, 15%; HPMC-0.5%, 0.75%) were prepared, choosing the same amount of the active polyphenol source L1. The physicochemical properties, rheological parameters, stability, and irritant effect on the rabbit corneal cell line (SIRC) were evaluated. Formulations in which P407 and HMPC concentrations were 10/0.75% and 12%/0.75% reached a gelation point close to the ocular surface temperature; the gels remained stable for 30 days and did not cause an irritant effect on the SIRC cell line.